Economic effects of a debt-to-income constraint in Finland: Evidence from Aino 3.0 model - Samu Kärkkäinen; Juho Nyholm (Bank of Finland, 2021)
We analyze the economic effects of a debt-to-income constraint for the Finnish economy. Our benchmark is a DSGE model which is designed to capture the most prominent features of the Finnish economy and is calibrated using Finnish macroeconomic data. The baseline model incorporates a loan-to-value type of constraint for new mortgage loans. We study the effects of replacing this with a neutral DTI constraint, neutral meaning that the level of the constraint is set so that it would not alter the mortgage loans-to-GDP ratio in the long run. We find that the replacement would have only small long run effects on the economy, and it would poten-tially reduce the volatility of several variables associated with the housing markets.
urn:nbn:fi:bof-202104281200
Keywords: 330; Suomen Pankki; Aino 3.0; DSGE; mallit; Suomi